2011
DOI: 10.1177/1091142111422436
|View full text |Cite
|
Sign up to set email alerts
|

Quality or Price? Evidence from ODA-Financed Public Procurement

Abstract: Infrastructure is essential for economic growth, and public procurement is an important instrument to use limited resources effectively. Among public procurers there remains a strong view that quality should not be compromised, particularly in high-value transactions, such as infrastructure projects. The common practice excludes incompetent applicants from the selection process. An alternative view is that infrastructure procurement can stimulate the economy by loosing qualification standards. The article exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…the winner's curse). Given these assumptions, it is suggested that an auctioneer can potentially alter the outcomes of an auction by lowering entry barriers, after which the more aggressive smaller bidders will obtain higher market shares, thereby lowering market concentration Ruzzier, 2009;Estache and Iimi, 2012;Kreiss et al, 2016;Welisch, 2018).…”
Section: Approaches To Counteract Market Concentrationmentioning
confidence: 99%
“…the winner's curse). Given these assumptions, it is suggested that an auctioneer can potentially alter the outcomes of an auction by lowering entry barriers, after which the more aggressive smaller bidders will obtain higher market shares, thereby lowering market concentration Ruzzier, 2009;Estache and Iimi, 2012;Kreiss et al, 2016;Welisch, 2018).…”
Section: Approaches To Counteract Market Concentrationmentioning
confidence: 99%
“…To overcome the potential effects of adverse selection in the choice of supplier, procurement systems tend to apply entry restrictions in the form of firm qualification schemes. It has been suggested that in a context of incomplete information about firms' capacities under the condition that technical, economic, and financial requirements defining the qualification scheme are adequate, qualification has beneficial effects on the functioning of the competitive system (Ancarani et al., 2016; Estache & Iimi, 2012; OECD, 2010). A qualification system is essentially static in the sense that once the contract is awarded it no longer acts to motivate the firm.…”
Section: Introductionmentioning
confidence: 99%
“…This may even be done to facilitate corruption, thus undermining the purpose of the debarment regime. 10 This section describes some common challenges.…”
Section: Debarment Practicesmentioning
confidence: 99%
“…12 According to Iimi (2011), who studied worldwide in- 10 The extra authority given to procurement agencies creates new risks of extortive corruption and facilitates what Rose-Ackerman (1978, chapter 4) describes as "milking suppliers"-i.e. given wide discretion associated with the rules, suppliers that could be debarred within the rules may avoid such a consequence by paying a bribe.…”
mentioning
confidence: 99%